Particulate Matter Increases the Severity of Bleomycin-Induced Pulmonary Fibrosis through KC-Mediated Neutrophil Chemotaxis - Cheng, I-Yin (Int J Mol Sci, 2019)
Background: Although particular matter (PM) increases incidence and severity of idiopathic pulmonary fibrosis, the underlying mechanism remains elusive. Methods: The effects of PM were evaluated in a murine model of bleomycin-induced pulmonary fibrosis. Mice were divided into four groups, receiving: (1) Saline (control), (2) bleomycin, (3) PM, or (4) bleomycin plus PM (Bleo+PM). Additional groups of Bleo+PM mice were treated with sivelestat (an inhibitor of neutrophil elastase) or reparixin (a C-X-C motif chemokine receptor 2 antagonist), or were genetically modified with keratinocyte chemoattractant (KC) deletion. Results: Pulmonary fibrosis was not observed in the control or PM groups. Bleomycin induced pulmonary fibrosis within 14 days. The Bleo+PM group showed worse pulmonary fibrosis when compared to the bleomycin group. Analyses of immune cell profile and chemokine/cytokine concentrations at day 2-bronchoalveolar lavage fluid (BALF) revealed that the Bleo+PM group had increased neutrophil number and elastase level and KC concentration compared to the bleomycin group. Neutrophil elastase activated the Smad2/Smad3/α-SMA pathway to induce collagen deposition, while sivelestat abrogated the increased severity of pulmonary fibrosis caused by PM. Chemotaxis assay revealed that BALF of the Bleo+PM group recruited neutrophil, which was dependent on KC. Further, genetic KC deletion or pharmaceutical inhibition of KC binding to CXCR2 with reparixin ameliorated the PM-induced increased severity of pulmonary fibrosis. Conclusions: These data provide evidence that the PM-induced increased severity of pulmonary fibrosis depends on KC-mediated neutrophil chemotaxis and give additional mechanic insight that will aid in the development of therapeutic strategies.